The Impact of EU Accession on Human Capital : Formation - Can Migration Fuel a Brain Gain? - Farchy, Emily (2012)
Can a brain drain be good for development? Many studies have established the theoretical possibility of such a brain gain. Yet it is only recently that the relaxation of data constraints has allowed for sound empirical assessments. In utilizing the dramatic policy change that accompanied European Union accession as a natural experiment, this paper is able to assuage fears of reverse causality between migration and human capital formation. The results highlight a significant impact of European Union accession on human capital formation indicating that the prospect of migration can indeed fuel skill formation even in the context of middle-income economies. And, if accompanied by policies to promote return migration, as well as a functioning credit market to enable private investment, international labor mobility could represent a powerful tool for growth.